2014
DOI: 10.1128/jcm.01152-14
|View full text |Cite
|
Sign up to set email alerts
|

First Report of bla NDM and bla OXA-58 Coexistence in Acinetobacter junii

Abstract: A cinetobacter species are a major cause of hospital-acquired infections, especially in intensive care units (ICUs) (1). This, in part, is due to the bacteria's ability to survive long-term on hospital environment surfaces and their ability to acquire antibiotic resistance genes (2). One of the Acinetobacter species most often associated with high morbidity and mortality is A. baumannii (1). However, other Acinetobacter species have also been associated with acquiring broad-spectrum antibiotic resistance genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The genome ACN21 was devoid of bla OXA-23 , while the presence of bla NDM-1 and bla OXA-420 could be encoding for carbapenem resistance. In ACN21, bla NDM-1 resides in chromosome and bla OXA-420 in plasmids whereas previous studies reported the co-presence of bla NDM and bla OXA-58 on the same plasmid [31][32][33][34]. In CIAT 758, bla OXA-58 was carried on the plasmid (Table 1).…”
Section: Resistance Determinantsmentioning
confidence: 95%
“…The genome ACN21 was devoid of bla OXA-23 , while the presence of bla NDM-1 and bla OXA-420 could be encoding for carbapenem resistance. In ACN21, bla NDM-1 resides in chromosome and bla OXA-420 in plasmids whereas previous studies reported the co-presence of bla NDM and bla OXA-58 on the same plasmid [31][32][33][34]. In CIAT 758, bla OXA-58 was carried on the plasmid (Table 1).…”
Section: Resistance Determinantsmentioning
confidence: 95%
“…Only the strains isolated in Malaysia and China have the bla OXA-58 and bla NDM-1 genes located on the same plasmid ( Alattraqchi et al, 2021 ; Liu et al, 2021 ) ( Figure 2B ), while in the Algerian isolate, the genes were chromosomally located ( Ramoul et al, 2016 ), and the genome of the Japanese strain is a draft ( Oinuma et al, 2016 ). Other non- baumannii Acinetobacter carrying bla OXA-58 and bla NDM-1 genes have been reported from Malaysia ( Alattraqchi et al, 2021 ), China ( Zhou et al, 2015 ; Chen et al, 2019 ; Li et al, 2022a , b ), and Palestine ( Regeen et al, 2014 ). Of these reports, three isolates were sequenced and found to carry these genes on the same plasmids ( Alattraqchi et al, 2021 ; Li et al, 2022a , b ) ( Figure 2B ).…”
Section: Discussionmentioning
confidence: 99%
“…Curiously in the same study, the authors noted that over the study period, a significant proportion of strains developed Colistin resistance (35%). Carbapenem-resistant A. junii infections have been recently reported in the literature [ 20 ].…”
Section: Discussionmentioning
confidence: 99%